Hematological parameters and nuclear abnormalities in peripheral erythrocytes of Achirus lineatus (Pleuronectiformes: Achiridae) - Prado, Lílian R. G. B.; Felix, Cristiane; Abessa, Denis M. S. [UNESP]; Buruaem, Lucas M.; Abujamara, Laís D.; Kirschbaum, Aline A.; Turatti, Gabriela C. R.; Ranzani-Paiva, Maria J. T.; Correia, Aristides T.; Seriani, Robson (Springer Nature, 2014)
Hematological parameter of demersal fish constitutes important measures of biological effects of seasonality and contaminants in sediments. We aimed to assess the hematological parameters and nuclear abnormalities, including micronuclei levels, in peripheral erythrocytes of flatfish Achirus lineatus collected in São Vicente Estuary in summer and winter. The number of lymphocytes was significantly higher in summer, whereas the number of neutrophils was significantly higher in winter. For other measured parameters, no significant differences were observed in spite of the levels of erythroblasts, leukocytes, thrombocytes, micronuclei and nuclear abnormality tended to be slightly higher in winter. Integrated analysis of data suggests that genotoxicity may be related to immunosuppression, although some types of leukocytes appear to act removing anomalous cells. Considering the contamination status of the Santos–São Vicente Estuarine system, the results provide an important contribution to knowledge of the hematological aspects of A.lineatus and its potential use as a bioindicator for monitoring estuarine sites.
Keywords: Biomarkers; Estuary; Flatfish; Hematology; Seasonality